Pelatihan penggunaan aplikasi Paint dan pembuatan blog untuk meningkatkan kreatifitas pendidik pada HIMPAUDI Batam Center - Nurul Azwanti; Alfannisa Annurullah Fajrin; Yopy Mardiansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Pendidikan Anak Usia Dini (PAUD) is the implementation of education before entering basic education to help growth and physical and spiritual development so that children have readiness in entering further education. The Association of Indonesian Early Childhood Educators and Education Personnel or abbreviated as HIMPAUDI is an organization of PAUD educators to increase the effectiveness of every PAUD teacher. Given the importance of the creativity of PAUD educators, HIMPAUDI Batam Center needs to make various innovative efforts to improve the quality of students and education itself. In this technological era, all forms of activities especially those related to teaching have turned to modern in order to keep up with the times. If only PAUD teachers feel that there is no need for creativity by not following technological developments especially considering that they have mastered learning in the classroom, then the educator will miss all the knowledge that is still embedded without being explored further using information technology. This service will provide training for PAUD teachers to innovate and increase their creativity without having to be outdated. Utilizing applications that are available free of charge and creating blogs as